Job Creation Law’s Risks towards Investment Efficiency And Business Convenience Regarding the Environment - Asnita Tresia Sitompul (Administrative and Environmental Law Review, 2022)
From the beginning, in the form of a Draft La,w until it was issued and passed into a Law, the Omnibus Law  Cipta Kerja caused a lot ocontroversiessy. Behind the efficiency of investment and convenience offered, UU Cipta K ja  is considered threatene eonmental sustainability and risk weakening law enforcement related to the environment. Therefore, this study aims to analyze and describe the risks posed by the UU Cipta Kerja on the environment from a legal perspective. The type of research used by the writer is descriptive exploratory research with a qualitative approach that aims to describe the nature of something that is taking place when research is carried out and examine the causes of a particular phenomenon and to d,escr the state of a phenomenon. To obtain dThection method was carried out by means of a putskak studyusinging data put skan reading materials such as books and websites. So that the authors find it easy to find data and information needed from various sources.